If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6+x=-7+2x
We move all terms to the left:
6+x-(-7+2x)=0
We add all the numbers together, and all the variables
x-(2x-7)+6=0
We get rid of parentheses
x-2x+7+6=0
We add all the numbers together, and all the variables
-1x+13=0
We move all terms containing x to the left, all other terms to the right
-x=-13
x=-13/-1
x=+13
| 28+7x=49+7x | | -17(y+3)+6(4y-3)=6(y-3)+14 | | 1x=11.75 | | 83=5(7-a)-a | | 3x+3-6=-9 | | x/2+17=17 | | 2x-2=-2x=12 | | 5f+9=12f-26 | | -3z-9=-42 | | -4x+6/7=2 | | 3x2-26x+32=0 | | 18x+x=205 | | 4(x+2)+8x=16 | | 17x+8=11x+6 | | -1/2x-5/3=-7/12 | | -7(5+3x)=-30-7x | | 30m+500=7,700 | | 60+5x2=140 | | -3+2k=k-1 | | -4-12=8x+24 | | 3x+900=2x+1000 | | 3/4=3/8x-2 | | -95=x-7(8+2x) | | 11÷7=2x | | -6y=2y+4=14 | | 3x+3=1x+(-5) | | 4(5x-7)=10x2 | | 5(2x+10)+30=6x+104 | | 5+4x-7=4x-22x | | -3(14+5r)2r=-14(r+3) | | 4(3x+8)=8+16 | | 24x+56=53x+56 |